Pengaruh Efikasi Diri Dan Komunikasi Terhadap Kinerja Karyawan - Ahmad Pauzi; Faizal Mulia Z; Kokom Komariah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of self-efficacy and communication on employee performance. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique used by the author is the census technique. PT. Ultimedia Group Saudara Sukabumi has 38 employees, and all employees are sampled. The data analysis technique used is multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient, simultaneous test (F test) and partial test (T test). The results of the study using the F test the probability value of sig. 0.00 < 0.05 which means that jointly self-efficacy (X1) and communication (X2) have a significant effect on employee performance (Y). While the t test shows that self-efficacy (X1) has a significant effect on employee performance (Y) and communication (X2) has a significant effect on employee performance (Y).